Depressive symptoms, parenting attitude, and violent discipline among caregivers of left-behind children in rural China: a cross-sectional study - Yunfei Qiu; Mengshi Li; Huifeng Shi; Chunxia Zhao; Yufeng Du; Xiaoli Wang; Jingxu Zhang (BMC Public Health, 2024)
Abstract Background The situation of mental health and discipline behaviors of left-behind children’s caregivers were not optimistic in rural China. Caregivers’ depression might increase the risk of using violent discipline. However, the specific ways in which depressive symptoms impact violent discipline have rarely been explored in rural areas. This study aims to assess the prevalence of violent discipline among left-behind children under 6 years of age in rural China and explore the potential mechanisms of how caregivers’ depressive symptoms affect violent discipline. Methods We enrolled a total of 396 pairs of left-behind children and their caregivers in our study, which was conducted in 5 counties of Hebei, Henan, Jiangxi, Guizhou, and Sichuan provinces in China. The depressive symptoms of caregivers were measured by using Zung Self-rating Depression Scale (ZSDS) and violent discipline was assessed by the Child Discipline Module of Multiple Indicator Cluster Surveys (MICS). A self-designed questionnaire was utilized to measure caregiver’s parenting attitude. Based on the cross-sectional data, controlling for potential confounders, structural equation modeling (SEM) was used to assess the direct and indirect effects of the mediation models by applying the weighted least squares with mean and variance adjusted (WLSMV) estimate. Results The prevalence of violent discipline, psychological aggression, and physical punishment was 72.7%, 59.3%, and 60.4% respectively of left-behind children under 6 years of age. According to the results of SEM, parenting attitude acted as a suppressor, suppressing the association between caregivers’ depressive symptoms and physical punishment/psychological aggression/violent discipline. The caregivers’ depressive symptoms positively influenced all the outcome variables by affecting parenting attitudes (p = 0.002, p = 0.013, p = 0.002). Conclusions The presence of depressive symptoms in caregivers increases the use of violent discipline through negative parenting attitudes. The mental health status of primary caregivers of left-behind children in rural China needed emphasis and improvement.